Development of Students Work Sheets (LKPD) with A Problem-Based Learning Model (PBM) in The Context of Riau Traditional Games in Circle Materials - Suci Nitia Edwar; Yenita Roza; Kartini Kartini (Universitas Riau, 2021)
This research is motivated by the lack of LKPD that provides steps that can guide students to understand the concept of material and the designed model is not appropriate to construct students' knowledge independently and there are no contextual problems that cause lack of interaction between students. LKPD will be more optimal if it is based on a learning model that teaches how to solve a problem. With the LKPD Problem Based Learning Model (PBM) students can gain learning experiences that teach real skills, investigation, and problem solving. The purpose of this study was to produce student worksheets (LKPD) through the application of the problem-based learning model (PBM) of SD Negeri 163 Pekanbaru students on circle material. This type of research is development research using the Borg & Gall model. The instruments in this study were validation sheets and student response questionnaires. The results of the study showed that the validity test of three validators on the syllabus was 91% with very valid criteria. While the practicality test for LKPD with a response questionnaire to six students showed an average percentage of 90.52% with the very practical category.